The Effect of Customer Service Quality on Customer Satisfaction at Nagari Syariah Bank Bukittinggi Branch - Yulita, Ratna; Illahi, Ilham (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2023)
This study aims to determine the influence of Customer Service Quality on Customer Satisfaction at Bank Nagari Syariah Bukittinggi Branch. Thus it can be used as a benchmark by banking companies to improve the quality of their services in the future. This research method is a type of quantitative research by collecting data using questionnaires distributed to customers at the Bukittinggi Branch of Nagari Syariah Bank with a total sample taken of 100 respondents. Data analysis techniques used are validation test, reliability test, normalist test, multicollinearity test, heteroscedasticity test, linearity test, simple regression analysis, coefficient of determination test, simultaneous effect test and partial test. From the results of processing the data obtained simple linear regression Y = 2.056 + 0.163X. the magnitude of the influence of service quality on customer satisfaction is 71.7%. From the simultaneous test calculations obtained F count of 252,070 (sig value 0.00 <0.05) which means that simultaneously there is a positive and significant influence between service quality on customer satisfaction. Then the results of partial calculations obtained t count of 15,877 (sig value 0.00 <0.05) which means that partial testing also has a positive and significant influence on customer satisfaction at Bank Nagari Syariah Bukittinggi Branch. The quality of customer service can provide more advantages for employees and companies. With the quality of this customer service, it is expected that customer satisfaction at Bank Nagari Syariah Bukittinggi Branch will increase.